LOCAL WISDOM IN PICTURES CONTAINED IN ENGLISH TEXTBOOKS: AN ANALYSIS OF ILLUSTRATIONS IN ENGLISH TEXTBOOKS FOR PRIMARY SCHOOL - Arasyid, Raskin Shiddiq (2013)
Understanding the nature of the relationship between language and culture is essential to the process of learning another language. Since textbooks and pictures are considered as effective teaching and learning aids, the present study is aimed at finding out how local wisdom derived from local culture is represented in the pictures contained in English textbooks for primary school. The study uses descriptive analysis which is qualitative in nature. Employing visual grammar framework as proposed by Kress and Van Leeuwen (2006) and the concept of culture in Four Dimensions proposed by Adaskou, Britten, and Fashi (1990), the study analyzes pictures contained in three English textbooks intended for seventh grade of primary school. The study found that the sociological sense of culture is dominating the distinctive occurrences of local culture represented in the pictures. Local wisdom derived from local culture is represented through family values (e,g, the role of family members, names, leisure activities, clothes, etc.). The study also found that the proportion of local culture representation is less than the representation of non-local culture. Keywords: picture analysis, local culture representation, visual grammar Supervisor : Fuad Abdul Hamied, Prof., Ph.D., M.A. Co-supervisor : Rojab Siti Rodliyah, M.Ed. Memahami prinsip dasar hubungan anatara bahasa dan budaya sangatlah penting dalam proses pembelajaran bahasa asing. Dikarenakan buku teks dan gambar telah dianggap sebagai alat bantu pembelajaran yang sangat efektif, penelitian ini ditujukan untuk mengetahui bagaimana kearifan lokal direpresentasikan dalam gambar yang terdapat pada buku teks bahasa Inggris untuk sekolah umum. Penelitian ini menggunakan analisa deskriptif yang mana merupakan penelitian kualitatif pada dasarnya. Dengan menggunakan visual grammar yang diprakarsai oleh Kress dan Van Leeuwen (2006) dan juga konsep budaya dalam empat dimensi oleh Adaskou, Britten, dan Fashi (1990), penelitian ini menganalisa gambar yang terdapat dalam tiga buku text bahasa Inggris untuk SMP kelas tujuh. Penelitian ini menemukan bahwa aspek sosiologis budaya mendominasi kemunculan budaya lokal yang terrepresentasikan di dalam gambar. Kearifan lokal, yang berdasarkan dari budaya lokal, terepresentasikan melalui nilai-nilai keluarga (contoh: peran anggota keluarga, nama, kegeiatan di waktu senggang, pakaian, dll). Penelitian ini juga menemukan bahwa proporsi dari representasi budaya lokal lebih sedikit dari representasi budaya asing. Kata kunci : analisa gambar, representasi budaya lokal, visual grammar Supervisor : Fuad Abdul Hamied, Prof., Ph.D., M.A. Co-supervisor : Rojab Siti Rodliyah, M.Ed.